National Identity, Public Goods, and Modern Economic Development - Stergios Skaperdas; Patrick A. Testa (Center for Economic Studies and ifo Institute (CESifo), 2023)
Early in their formation, modern nation-states face internal conflicts that impede their economic development. This paper examines the role of national identity in helping modern states overcome such conflicts to provide public goods and grow. We develop a model in which the population can identify with the nation or with an alternative identity (e.g., ethnic, class), where identity confers some psychological benefit from a group's status. We show that elites have an incentive to induce commoners to identify with the nation. The more commoners identify with the nation, the less is conflict between elites and commoners, and the more revenues can be collected and public goods broadly provided. This effect is self-reinforcing: the greater is public goods provision, the larger is the national income and thus the status benefit from national identification. Elites' incentives to induce national identification, however, depend on the presence of fiscal restraints on the elite. We provide two pieces of evidence consistent with the theory. First, we revisit the development of the English state, identifying a central role for national identity therein. Second, we build a novel time-varying measure of national identification for countries, which we show to be positively associated with public goods provision and economic performance, particularly for more democratic countries.
Keywords: D74; H10; H50; O10; O43; P14; 330; national identity; public goods; conflict; development and growth